2017
DOI: 10.3390/en10020158
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shale Gas on the Cost and Feasibility of Meeting Climate Targets—A Global Energy System Model Analysis and an Exploration of Uncertainties

Abstract: There exists considerable uncertainty over both shale and conventional gas resource availability and extraction costs, as well as the fugitive methane emissions associated with shale gas extraction and its possible role in mitigating climate change. This study uses a multi-region energy system model, TIAM (TIMES integrated assessment model), to consider the impact of a range of conventional and shale gas cost and availability assessments on mitigation scenarios aimed at achieving a limit to global warming of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The international focus on greenhouse gas emissions from the oil and gas industry is expected to be intensified to limit the global warming. This is especially important for production, transport as well as end consumers of products that may result in methane emissions [31][32][33][34]. The present study contributes to reduce the emissions at land based mid-stream facilities, where it is shown that identifying and repairing "super-emitters" would give a high benefit cost ratio.…”
Section: Discussionmentioning
confidence: 77%
“…The international focus on greenhouse gas emissions from the oil and gas industry is expected to be intensified to limit the global warming. This is especially important for production, transport as well as end consumers of products that may result in methane emissions [31][32][33][34]. The present study contributes to reduce the emissions at land based mid-stream facilities, where it is shown that identifying and repairing "super-emitters" would give a high benefit cost ratio.…”
Section: Discussionmentioning
confidence: 77%
“…Few et al [12] apply a global energy system model to examine the effects of high levels of shale gas production on the costs of meeting a climate change target of 2 °C above preindustrial levels by 2100. They find that if globally coordinated action to reduce emissions is taken, abundant shale gas does not substantially reduce the costs of achieving the goal.…”
Section: Recent Literaturementioning
confidence: 99%
“…The health impacts of UOG are well documented. As a fossil fuel, UOG elevates the long-term global environmental health impacts associated with climate change (through fugitive methane emissions, and contributions to the total carbon budget) [3], although gas has a lower carbon footprint to coal, produces lower NOx, SO2, black carbon, CO, mercury and particulates than the shale gas lifecycle at a mass per energy base and so is often framed as a transition fuel for short-term decarbonisation of fossil-fuel based energy systems [4]. Yet despite its environmental performance relative to coal, there remain a number of environmental health impacts from UOG that are both local and immediate.…”
Section: Primary Environmental Impactsmentioning
confidence: 99%